Scandinavia - Time-Life Books (Alexandria, Va. : Time-Life Books, 1985)
An introduction to the geography, history, economy, government, and people of Denmark, Norway, Sweden, Iceland, and Finland.
Maps on lining papers.
Includes index.
Bibliography: p. 156-157.
Keywords: Scandinavia; Scandinavia